Spirituele vorming om 'n missionale karakter in gemeentes in die praktyk te bewerkstellig - Pretorius, Philippus C.; Niemandt, Cornelius J. P. (Verbum et Ecclesia, 2018)
Spiritual formation to bring about a missional character in congregations in practice. This study applied literature review to focus on missional ecclesiology and, more specifically, on the important role and impact of spirituality in supporting a missional church. Although the research originated in reformed churches in South Africa, the reflection on the relation between the concept of missional church and a Christian spirituality, and the practical examples that illustrate such a missional spirituality, transcend the context and is applicable to most contexts. The conclusion of the research affirmed a Trinitarian approach to spirituality and the indispensable place of a missional spirituality for Christian congregations. A life in the Trinity forms and informs everyday life. It encourages disciples of Christ to participate in God's mission. There is no difference between Christian spirituality and missional spirituality. One of the key findings was the important role of habits: believers should change their habits in their everyday life in order to change their thoughts, and not the other way around. Practical examples of habits are as follows: systematic reading of God's Word; to see what God sees; kenosis shown through hospitality; faith discernment with other believers; associating the everyday normalities as spiritual; finding rest in God; and eating together. Intradisciplinary and/or Interdisciplinary implications: This article was written from the perspective of mission studies. The contextual challenge was to emphasise the importance of habits in Christian spirituality, and the reciprocal relationship between spirituality and being a missional church. This article has challenged the culture of church-organised mission projects. (Afrikaans)
free